Peningkatan Kesegaran Jasmani dengan Metode Permainan Beregu pada Siswa Kelas V SDN Condongcatur Yogyakarta - Ari Iswanto (LPPM Press, 2015)
This research aimed at determining whether the Team Game method can increasephysical fitness on the fifth grade students of Yogyakarta Muhammadiyah elementaryschool Condongcatur. The research was carried out in Yogyakarta Muhammadiyahelementary school Condongcatur from July to October 2014. Further, the subject of thisresearch was the fifth grade students of Yogyakarta Muhammadiyah elementary schoolCondongcatur schooling year 2014-2015 consisting of 40 students who are 21 maleand 19 female students. This research implemented Classroom Action Research (CAR)within the analysis by comparing the precondition of students, test results after the firstcycle and test results after the second cycle. Based on the research findings, it could beconcluded that the team game method could be used as an attempt to increase the physicalfitness of students on the fifth grade elementary school children Condongcatur YogyakartaMuhammadiyah schooling year 2014/2015 which was proved from the study that has beencarried out in the first cycle and the second cycle. Almost all students experienced thesignificant increase in physical fitness. This was also proved that after the first cycle test,there is only one student whose physical fitness test is less. After the second cycle was thencarried out, there is no longer student of whose physical fitness test is low